Anomalous shift of the recombination energy in single asymmetric quantum wells - Dantas, Noelio Oliveira (2002)
Self-consistent numerical calculation and photoluminescence (PL) measurements have been used to investigate the temperature dependence of the optical Stark effect in n-doped GaAs/AlGaAs single asymmetric quantum wells (SAQWs), grown by molecular beam epitaxy. In the low-temperature regime (5 to 40 K) a remarkable blue shift (9.8 meV) is observed in the PL peak energy, as the optical excitation intensity increases from 0.03 to 90 W/cm2. The blue shift is well explained by the reduction of the two-dimensional electron gas (2DEG) density, due to a charge-transfer mechanism. At about 80 K, however, an anomalous behavior of the PL peak energy was found, i.e. a red shift has been observed as the optical excitation intensity increases. This anomalous behavior has been explained by combining the effects of band gap renormalization, band bending, temperature dependence of the band gap, temperature dependence of the 2DEG density, and temperature dependence of the fundamental energy position.